Topographic anatomy of the insular region - (:unkn) unknown (AMER ASSOC NEUROLOGICAL SURGEONS, 1999)
abject. The insula is one of the paralimbic structures and constitutes the invaginated portion of the cerebral cortex, forming the base of the sylvian fissure. The authors provide a detailed anatomical study of the insular region to assist in the process of conceptualizing a reliable surgical approach to allow for a successful course of surgery. Methods. The topographic anatomy of the insular region was studied in 25 formalin-fixed brain specimens (50 hemispheres). The periinsular sulci (anterior, superior, and inferior) define the limits of the frontoorbital, frontoparietal, and temporal opercula, respectively. The opercula cover and enclose the insula. The limen insula is located in the depths of the sylvian fissure and constitutes the anterobasal portion of the insula. A central insular sulcus divides the insula into two portions, the anterior insula (larger) and rbe posterior insula (smaller). The anterior insula is composed of three principal short insular gyri (anterior, middle, and posterior) as well as the accessory and transverse insular gyri. All five gyri converge at the insular apex, which represents the most superficial aspect of the insula. The posterior insula is composed of the anterior and posterior long insular gyri and the postcentral insular sulcus, which separates them. The anterior insula was found to be connected exclusively to the frontal lobe, whereas the posterior insula was connected to both the parietal and temporal lobes. Opercular gyri and sulci were observed to interdigitate within the opercula and to interdigitate the gyri and sulci of the insula. Using the fiber dissection technique, various unique anatomical features and relationships of the insula were determined. Conclusions. The topographic anatomy of the insular region is described in this article, and a practical terminology for gyral and sulcal patterns of surgical significance is presented. This study clarifies and supplements the information presently available to help develop a more coherent surgical concept.
Keywords: insula; limbic system; anatomical study; operculum; paralimbic system; sylvian fissure; APHASIA; 2ND